Serovar distribution of urogenital C trachomatis isolates in Germany. Issue 2 (April 1991) - Näher, H; Petzoldt, D
Abstract : Using monoclonal antibodies in a microimmunofluorescence test the distribution of C trachomatis serovars isolated in the STD out-patient clinic of the Department of Dermatology of the University of Heidelberg was determined. Of 56 isolates investigated the most frequent was serovar E with 35.7%, followed by serovar D with 28.6% and serovar F with 26.8%. This shows that the distribution of C trachomatis in Germany is very similar to that in other Western countries.